1992
DOI: 10.1002/pro.5560010904
|View full text |Cite
|
Sign up to set email alerts
|

Multiple phosphate positions in the catalytic site of glycogen phosphorylase: Structure of the pyridoxal‐5′‐pyrophosphate coenzyme‐substrate analog

Abstract: The three-dimensional structure of an R-state conformer of glycogen phosphorylase containing the coenzymesubstrate analog pyridoxal-5'-diphosphate at the catalytic site (PLPP-GPb) has been refined by X-ray crystallography to a resolution of 2.87 A. The molecule comprises four subunits of phosphorylase related by approximate 222 symmetry. Whereas the quaternary structure of R-state PLPP-GPb is similar to that of phosphorylase crystallized in the presence of ammonium sulfate (Barford, D. & Johnson, L.N., 1989, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
(71 reference statements)
1
17
0
Order By: Relevance
“…This position also corresponds to the position observed for orthophosphate binding to T-state GPa (Withers et al, 1982). As previously discussed, this site is unlikely to be a productive site for the reaction pathway Sprang et al, 1992). Only under the constraints of the additional methyl group in the 0 configuration in heptulose-2-P is the phosphate directed down toward the cofactor phosphate or in the compound glucose-1,2-cyclicphosphate (Jenkins et al, 1981;Withers et al, 1982).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This position also corresponds to the position observed for orthophosphate binding to T-state GPa (Withers et al, 1982). As previously discussed, this site is unlikely to be a productive site for the reaction pathway Sprang et al, 1992). Only under the constraints of the additional methyl group in the 0 configuration in heptulose-2-P is the phosphate directed down toward the cofactor phosphate or in the compound glucose-1,2-cyclicphosphate (Jenkins et al, 1981;Withers et al, 1982).…”
Section: Discussionsupporting
confidence: 64%
“…The regulation of glycogen phosphorylase either by kinase-promoted phosphorylation on Ser 14 or by noncovalent binding of effectors (such as AMP, glucose-6-phosphate, glucose) may be understood to a first approximation in terms of the Monod, Wyman, and Changeux theory in which the enzyme exists in 2 (or at least 2) states: a T state with low affinity for substrates and low activity, and an R state with high affinity and high activity. X-ray structural studies have defined the conformations of T and R states for both phosphorylase b and phosphorylase a (Sprang & Fletterick, 1979;Sprang et al, 1988Sprang et al, , 1991Acharya et al, 1991;Barford et al, 1991) and the binding sites for different ligands (e.g., Johnson et al, , 1992Johnson et al, , 1993Oikonomakos et al, 1991;Johnson, 1992). The present experiments on catalysis in the crystal were performed with T-state GPb crystals in which the enzyme is known to be active but with reduced activity and lower affinity for substrate than the R form of the enzyme (Kasvinsky & Madsen, 1976).…”
mentioning
confidence: 99%
“…In the electrophilic mechanism, a closer association between the cofactor and substrate phosphates is required than has been observed in the crystallographic results to date. Such a close approach is mimicked by PLDP, but the structural studies on the R-state GPb-PLDP complexes (Leonidas et al, 1992b;Sprang et al, 1992) showed no evidence of additional strong interactions with the cofactor 5"phosphate that have been invoked to provide stabilizing energy for the constrained activator dianion (Chang et al, 1983;Madsen & Withers, 1986;Sprang et al, 1992) as one might have expected on the basis of this mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…It is interesting that Glc does not bind to the PL-GPb in the T state in the absence of anion, and vice versa. DPL-GPb, PLPMe-GPb, and PLDP-GPb cannot be crystallized in the T-state form, possibly because Glc cannot bind (or binds weakly) to these enzymes (Yan et al, 1979;Withers et al, 198213;Leonidas et al, 1992b;Sprang et al, 1992;Oikonomakos et al, unpubl.). Thus, any substitutions of PLP that favor the formation of Glc binding site are expected to trigger the R-to T-state conformation change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation